2013
DOI: 10.1542/peds.2012-1496
|View full text |Cite
|
Sign up to set email alerts
|

Physician Advice to Adolescents About Drinking and Other Health Behaviors

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Evidence regarding effectively screening and counseling adolescents about unhealthy alcohol use is accumulating. Young adults aged 18 to 24, those most at risk for excess alcohol consumption, are often not asked or counseled by physicians about unhealthy alcohol use. WHAT THIS STUDY ADDS:In 2010 among US 10th graders (age 16), 36% drank, 28% binged, and 23% were drunk in the past month; although 82% saw a doctor, 54% were asked about drinking but only 17% were advised to reduce or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 27 publications
2
30
1
Order By: Relevance
“…Despite recommendations by the World Health Organization 14 and American Academy of Pediatrics [15][16][17] that all adolescents receive screening for ATOD use, most adolescent medicine providers do not follow these best practice guidelines. [18][19][20][21] Existing instruments for screening adolescents' ATOD use have notable limitations. The CRAFFT, a brief screening instrument recommended by the American Academy of Pediatrics, 17 has a number of strengths, including its brevity and good psychometric properties, 22 To assist pediatricians in identifying adolescents at risk for alcohol-related problems, the National Institute on Alcohol Abuse and Alcoholism (NIAAA) developed a brief screening instrument 27 that asks patients about their frequency of drinking in the past year and that of their friends.…”
Section: Discussionmentioning
confidence: 99%
“…Despite recommendations by the World Health Organization 14 and American Academy of Pediatrics [15][16][17] that all adolescents receive screening for ATOD use, most adolescent medicine providers do not follow these best practice guidelines. [18][19][20][21] Existing instruments for screening adolescents' ATOD use have notable limitations. The CRAFFT, a brief screening instrument recommended by the American Academy of Pediatrics, 17 has a number of strengths, including its brevity and good psychometric properties, 22 To assist pediatricians in identifying adolescents at risk for alcohol-related problems, the National Institute on Alcohol Abuse and Alcoholism (NIAAA) developed a brief screening instrument 27 that asks patients about their frequency of drinking in the past year and that of their friends.…”
Section: Discussionmentioning
confidence: 99%
“…Between 36% and 50% of high school students currently drink alcohol, and 28% to 60% of them report binge drinking. 13,14 Nearly two-thirds of these students reported binge drinking on more than one occasion in the past 30 days. One in 10 high school seniors report drinking 10 or more drinks in a row, and 5.6% of high school seniors report consuming 15 or more drinks in a row.…”
Section: Epidemiology Of Binge Drinkingmentioning
confidence: 99%
“…However, in a meta-analysis of over 185 studies by Tanner-Smith and Lipsey (2015), the authors found extensive empirical support for this intervention for adolescents and young adults. Recent national surveys have found most adults are not screened and counseled about alcohol in adult primary care (Hingson et al 2012; Hingson et al 2013), particularly young adults ages 18–24, those most likely to exceed low-risk guidelines and meet alcohol dependence criteria in the past year. The literature on SBIRT lists several barriers to implementation including the time required to ask questions and to counsel, the lack of provider training, treatment and referral resources, and reimbursement difficulties.…”
Section: Five Important But Not Highest Priority Strategiesmentioning
confidence: 99%